PEMBINAAN TEKNOLOGI INFORMASI DAN SISTEM OPERASIONAL BANK SYARIAH - Koko Handoko; Wasiman Wasiman; Pastima Simanjuntak (ASOSIASI IDEBAHASA KEPRI, 2022)
Information technology is a knowledge that is always evolving from tools or communication which is a delivery of information through rapid communications, which relates to information problems in terms of all aspects ranging from data collection, data storage, data processing from information to the process of delivering information to people who need it. The purpose of fostering information technology and healthy internet use is an educational process by providing sufficient understanding of the current latest technology and being educated with the Islamic bank operating system, the owner of the fund invests his money so he can earn interest from the bank. If the profit sharing from the customer's funds is then distributed to those in need (eg venture capital), with a profit sharing agreement according to the agreement. Guidance on the Development of Information Technology and Bank Sariah Operational Systems at the Vocational High School Nang Nadim Batam to find out how to use good information technology and know the operating system of the Sariah bank. With this coaching, it is hoped that students will be helped in understanding the service that was carried out on January 15 and 16, 2019 at SMK Hang Nadim Batu Aji, Batam City.